TREE SPECIES DIVERSITY IN THE LOWLAND FOREST OF THE CORE ZONE OF THE BUKIT DUABELAS NATIONAL PARK, JAMBI, INDONESIA - RAHMAH, RAHMAH; KARTAWINATA, KUSWATA; NISYAWATI, NISYAWATI; WARDHANA, WISNU; NURDIN, ERWIN (REINWARDTIA, 2016)
RAHMAH, KARTAWINATA, K., NISYAWATI, WARDHANA, W. & NURDIN, E. 2016. Tree species diversity in the lowland forest of the core zone of the Bukit Duabelas National Park, Jambi, Indonesia. Reinwardtia 15(1): 11 - 26. â An analysis of the composition and structure of a one-hectare plot of forest on a lowland hill slope in the eastern core zone of the Bukit Duabelas National Park, Jambi, was conducted in October and November 2012. The objective of the study was to obtain a descriptive account of the structure and tree species composition of a lowland forest in the eastern core zone of the park. The plot was divided into 100 subplots ofÂ  (10 m Ã 10 m) each and the seedling subplots (5 m Ã 5 m) were nested in the sapling subplots. A total of 414 trees were recorded with DBH (Diameter at Breast Height) ?10 cm, representing 113 species and 38 families, with the total BA (Basal Area)Â  of 25.71 m2 and Shannon- Wiener diversity index of 4.29. Prunus arborea with IV (Importance Value) of 19.19 is the dominant species and the other prevalent species were, Dracontomelon dao (IV =11.46) and Hydnocarpus sp. (IV =11.38). A total of 44 species (38.9%) had each density of 1 tree/ha, which may be considered locally rare. Ficus fistulosa had the highest density (24 trees/ha) and Prunus arborea had the highest BA (3.28 m2 = 12.8% of the total). Only 10 species had F (frequency) of 8-18%, of which Hydnocarpus sp. had the highest (18%); the remaining species had F<8%, which may be considered locally rare. Moraceae (IV= 34.05) was the dominant family. The two richest families were Moraceae (11) and Clusiaceae (9). A total of 61 species were registered in the Sumatra checklist and one of them was endemic (Baccaurea dulcis). A total of 13 species are listed in the IUCN Red List. The forest is a developing community after disturbance in the past with poor regeneration. Species with complete representation of trees, saplings and seedlings will probably remain in the forest in the future.